Bulk and epitaxial growth of silicon carbide. Issue 2 (June 2016) - Kimoto, Tsunenobu
Abstract: Silicon carbide (SiC) is a wide bandgap semiconductor having high critical electric field strength, making it especially attractive for high-power and high-temperature devices. Recent development of SiC devices relies on rapid progress in bulk and epitaxial growth technology of high-quality SiC crystals. At present, the standard technique for SiC bulk growth is the seeded sublimation method. In spite of difficulties in the growth at very high temperature above 2300 °C, 150-mm-diameter SiC wafers are currently produced. Through extensive growth simulation studies and minimizing thermal stress during sublimation growth, the dislocation density of SiC wafers has been reduced to 3000–5000 cm −2 or lower. Homoepitaxial growth of SiC by chemical vapor deposition has shown remarkable progress, with polytype replication and wide range control of doping densities (10 14 –10 19  cm −3 ) in both n- and p-type materials, which was achieved using step-flow growth and controlling the C/Si ratio, respectively. Types and structures of major extended and point defects in SiC epitaxial layers have been investigated, and basic phenomena of defect generation and reduction during SiC epitaxy have been clarified. In this paper, the fundamental aspects and technological developments involved in SiC bulk and homoepitaxial growth are reviewed.